Can permanganate oxidizable carbon, microbial respiration, and carbon mineralization rate reflect carbon dynamics across land use and pedo-climate gradients in West African semi-arid zones? - Nadjire, Gannouka; Bandaogo, Alimata Arzouma; Gebremichael, Amanuel W.; Ouédraogo, Oumarou; Boussim, Joseph Issaka (Frontiers in Soil Science, 2025)
Climate variability, soil type, land use, and vegetation structure modulate soil organic carbon (SOC) dynamics, but their effects on sensitive soil carbon indicators are not adequately quantified in semi-arid ecosystems. This research examined the independent and synergistic impacts of pedo-climate, land use, and canopy cover on permanganate oxidizable carbon (POXC), soil microbial respiration (CO2-C), and the carbon mineralization rate (CMR) in the semi-arid regions of West Africa to determine their effectiveness as indicators of soil carbon dynamics. We collected 480 composite soil samples across Sudanian and Sudano-Sahelian zones, covering three land use types (cropland, fallow, protected area), two canopy positions (subcanopy, intercanopy), and two depths (0–10 cm, 10–30 cm). POXC, CO2-C, and SOC concentrations were analyzed, and CMR was derived from CO2-C per unit SOC. The indicators exhibited distinct sensitivities, with POXC responding primarily to pedo-climate and canopy cover. CO2-C was influenced by all factors with depth-amplified variation, and CMR was most sensitive to land use and canopy position in topsoil but shifted to pedo-climatic control at depth. The fixed effects explained a small portion (14% to 16%) of topsoil (0–10 cm) variance, indicating significant unmeasured variability sources. Depth-moderated indicator relationships, POXC–SOC correlations weakened with depth, whereas CO2-C–CMR associations strengthened, indicating a transition from surface labile carbon control to deeper microbial and nutrient constraints. Critically, the indicators provide complementary, depth‑explicit information; POXC and SOC contextualize pool size and labile availability, whereas CO2-C and CMR assess the functional accessibility and energetic feasibility of decomposition. Therefore, these metrics are best used jointly to signal early changes rather than as stand-alone indicators. Future work should identify additional drivers to enhance capacity across depths and contexts.